VIROTHERAPY WITH NEWCASTLE DISEASE VIRUS IMPROVES HISTOPATHOLOGICAL PICTURE OF RATS LUNGS WITH FIBROSARCOMA - Amelia, Ni Kadek Shita; Adi, Anak Agung Ayu Mirah; Winaya, Ida Bagus Oka (Buletin Veteriner Udayana, 2023)
Fibrosarcoma is a malignant tumor that originates from fibrous connective tissue which generally grows in the soft tissue inside or subcutaneously. Common cancer treatments today, such as chemotherapy, have side effects on healthy cells. One of the alternative therapy that has been extensively researched today is virotherapy using the Newcastle Disease virus. This study aimed to determine the effect of virotherapy with Newcastle Disease virus on the histopathological appearance of the lungs of rats with fibrosarcoma. This study used a completely randomized design (CRD) which consisted of two treatments. Treatment group 0 (P 0 ) was then injected with PBS in the amount of 0.5 mL and treatment group 1 (P 1 ) was injected with the Newcastle Disease virus in a dose of 0.5 mL/2 8 HA units. Two weeks after treatment, euthanasia was performed. Lung samples were then made histopathological slides and observed microscopically for hemorrhagic lesions, necrosis, and edema. From the results of both treatments, were found necrosis and hemorrhage, with no edema lesions. Data analysis used the Mann-Whitney test. The analysis found a difference in the mean necrotic and hemorrhagic lesions between P 0 and P 1 (P=0.050) where the number of these lesions decreased. Based on the results obtained, it can be concluded that virotherapy with Newcastle Disease virus can improve the histopathological picture of the lungs. Therefore, it is necessary to conduct research that compares the effectiveness of virotherapy with conventional therapy in suppressing fibrosarcoma.